2010
DOI: 10.1097/brs.0b013e3181e03577
|View full text |Cite
|
Sign up to set email alerts
|

Charcot Arthropathy of the Lumbar Spine Treated Using One-Staged Posterior Three-Column Shortening and Fusion

Abstract: A single-stage, multilevel, posterior 3-column resection and primary shortening can be a useful surgical strategy in symptomatic patients with Charcot arthropathy of the spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Because of her multiple anterior surgeries for scoliosis, the authors concluded an anterior approach would produce significant risk to the vessels adjacent to the Charcot segment, due to inflammatory adhesion. [ 21 ] The single-stage, posterior 3-column resection approach used by the authors provides ventral access to the affected vertebral bodies without transecting the thecal sac, through ligation of nonfunctional roots within the Charcot segment. [ 21 ] By permitting direct host-to-host bony contact, the procedure eliminates the need for anterior and posterior column struts, while reducing the number of graft-host sites for the bone union.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of her multiple anterior surgeries for scoliosis, the authors concluded an anterior approach would produce significant risk to the vessels adjacent to the Charcot segment, due to inflammatory adhesion. [ 21 ] The single-stage, posterior 3-column resection approach used by the authors provides ventral access to the affected vertebral bodies without transecting the thecal sac, through ligation of nonfunctional roots within the Charcot segment. [ 21 ] By permitting direct host-to-host bony contact, the procedure eliminates the need for anterior and posterior column struts, while reducing the number of graft-host sites for the bone union.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] The single-stage, posterior 3-column resection approach used by the authors provides ventral access to the affected vertebral bodies without transecting the thecal sac, through ligation of nonfunctional roots within the Charcot segment. [ 21 ] By permitting direct host-to-host bony contact, the procedure eliminates the need for anterior and posterior column struts, while reducing the number of graft-host sites for the bone union. The authors believe the single-stage, posterior 3-column resection with primary shortening approach avoids the potential complications of a long anterior cage or allograft segment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A situation where there is a complete transection of the spinal cord with absence of neural elements at the site of the Charcot joint would also facilitate direct access to the anterior column through a single posterior incision2,4,12).…”
Section: Discussionmentioning
confidence: 99%